2015
DOI: 10.1038/srep12072
|View full text |Cite
|
Sign up to set email alerts
|

The making of a branching annelid: an analysis of complete mitochondrial genome and ribosomal data of Ramisyllis multicaudata

Abstract: Ramisyllis multicaudata is a member of Syllidae (Annelida, Errantia, Phyllodocida) with a remarkable branching body plan. Using a next-generation sequencing approach, the complete mitochondrial genomes of R. multicaudata and Trypanobia sp. are sequenced and analysed, representing the first ones from Syllidae. The gene order in these two syllids does not follow the order proposed as the putative ground pattern in Errantia. The phylogenetic relationships of R. multicaudata are discerned using a phylogenetic appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
88
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(91 citation statements)
references
References 53 publications
(81 reference statements)
2
88
0
1
Order By: Relevance
“…that inhabit practically all marine benthic realms (Aguado et al 2015b). Surprisingly, Aguado et al (2015a) found that the gene order of the two investigated syllids (Ramisyllis multicaudata and Trypanobia cryptica) was completely different from the ground pattern proposed for Pleistoannelida. However, since these were the first two mt genomes from syllids, the authors could not assess if Syllidae in general or only members of the more recent clade including Ramisyllis and Trypanobia show these different gene orders.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…that inhabit practically all marine benthic realms (Aguado et al 2015b). Surprisingly, Aguado et al (2015a) found that the gene order of the two investigated syllids (Ramisyllis multicaudata and Trypanobia cryptica) was completely different from the ground pattern proposed for Pleistoannelida. However, since these were the first two mt genomes from syllids, the authors could not assess if Syllidae in general or only members of the more recent clade including Ramisyllis and Trypanobia show these different gene orders.…”
Section: Introductionmentioning
confidence: 67%
“…Occasionally, some genes of Streptosyllis sp., T. antoni and Typosyllis sp. end in TA or simply T. These variations from the typical stop and start codons have been also found in R. multicaudata and T. cryptica (Aguado et al 2015a), and incomplete stop codons are also present in other annelids (Bleidorn et al 2006;Li et al 2016). Interestingly, alternative start and stop codons only appear in those syllids with highly rearranged genomes (i.e.…”
Section: Brachycephala the Most Common Base Is T (Values Around 4mentioning
confidence: 72%
See 3 more Smart Citations